Dnase1L3 Regulates Inflammasome-Dependent Cytokine Secretion - Shi, Guilan; Abbott, Kennady N.; Wu, Wenbo; Salter, Russell D.; Keyel, Peter A. (Frontiers in Immunology, 2017)
Pediatric-onset systemic lupus erythematosus arises in humans and mice lacking the endonuclease Dnase1L3. When Dnase1L3 is absent, DNA from circulating apoptotic bodies is not cleared, leading to anti-DNA antibody production. Compared to early anti-DNA and anti-chromatin responses, other autoantibody responses and general immune activation in Dnase1L3-/- mice is greatly delayed. We investigated the possibility that immune activation, specifically inflammasome activation, is regulated by Dnase1L3. Here we report that Dnase1L3 inhibition blocked both NLRP3 and NLRC4 inflammasome-mediated release of High Mobility Group Box 1 protein and IL-1β. In contrast to IL-1β release, Dnase1L3 inhibition only mildly impaired NLRP3-dependent pyroptosis, as measured by propidium iodide uptake or LDH release. Mechanistically, we found that Dnase1L3 was needed to promote ASC nuclear export and speck formation. Our results demonstrate that Dnase1L3 inhibition separates cytokine secretion from pyroptosis by targeting ASC. These findings suggest that Dnase1L3 is necessary for cytokine secretion following inflammasome activation.